Development of Virtual Reality Games with an Ethnomathematics Approach of Batam Culture for Elementary School Social Arithmetic Materials (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This research develops a virtual reality-based game with an ethnomathematics approach to Batam City culture in the form of Luti Gendang food in learning social arithmetic material in mathematics learning at the elementary school level. This product's development is significant because students are now a digitally native generation and are more interested in learning through technological media than traditional media. Using the ADDIE model as a basis, this research will focus on the development stage, which includes 3 steps, namely (1) initial product design in the form of making storyboards, making learning videos with Adobe Premiere Pro, designing image designs for VR displays, and making learning videos; (2) initial product development focuses on making VR games and conducting validation tests by experts covering the feasibility of material, media, and language to determine the feasibility of the media being developed, and (3) refining the initial product by making revisions and improvements based on the results of the validation test. The development findings demonstrate that: (1) The initial product design incorporates five key menus—VR Simulation, Material, Video, Quiz, and Info; (2) The expert evaluations of the product’s feasibility across media, language, and content aspects yielded average scores of 85.2, 80.8, and 83.1, respectively, classifying the product’s overall feasibility as excellent; and (3) Subsequent refinements were implemented based on expert validation and user testing feedback, specifically targeting interactivity enhancements, improvements to VR visual elements, and adjustments to in-VR narrations and directional cues.